2013
DOI: 10.2134/agronj2012.0454
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Polymer‐Coated Urea and Urea Fertilizer Mixtures on Spring Wheat Protein Concentrations and Economic Returns

Abstract: The economic benefit of using controlled-release N fertilizers on hard red spring wheat (HRSW, Triticum aestivum L.) depends on its cost/price ratio, grain yield, and availability of discount and/or premium prices for protein concentration. The objective of this study was to evaluate the effect of five different proportions (0, 25, 50, 75, and 100%) of polymer-coated urea (PCU) in the N fertilizer mixture applied at three different N rates on (i) HRSW grain yield and protein concentration and (ii) whole-plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 19 publications
(30 reference statements)
4
26
0
Order By: Relevance
“…Likewise, at the tested 225 kg N ha −1 rate, cabbage marketable yield was not affected by N source (soluble N vs. various CRF) and timing (preplant vs. split-applied) in seven out of nine environments. When N treatment was significant (p < 0.05), marketable cabbage yield was lower with CRF than ANs, as was observed by others (Grant et al 2012;Farmaha and Sims 2013). Overall, we observed that the quantity of fertilizer N to maximize Note: Within a column and site, values with different lowercase letters represent statistical differences based on protected leas significant means separation.…”
Section: Discussionsupporting
confidence: 77%
“…Likewise, at the tested 225 kg N ha −1 rate, cabbage marketable yield was not affected by N source (soluble N vs. various CRF) and timing (preplant vs. split-applied) in seven out of nine environments. When N treatment was significant (p < 0.05), marketable cabbage yield was lower with CRF than ANs, as was observed by others (Grant et al 2012;Farmaha and Sims 2013). Overall, we observed that the quantity of fertilizer N to maximize Note: Within a column and site, values with different lowercase letters represent statistical differences based on protected leas significant means separation.…”
Section: Discussionsupporting
confidence: 77%
“…It suggests that the chosen cultivars were more efficient in low yielding years at partitioning a greater proportion of total dry matter and total N to the grain. In 2011 and 2012, ANUE was found very low for each N rate treatment (∼ 18, 10, and 9 kg grain kg −1 N fertilizer for low, medium, and high N fertility treatments, respectively) than ANUE for similar N rates found in the region (∼ 30, 22, and 14 kg grain kg −1 N fertilizer for low, medium, and high N fertility treatment, respectively, Farmaha and Sims, 2013b). The values of NUPE and NUTE found in this study were close to the published values (Muurinen et al, 2007) for spring wheat.…”
Section: Resultsmentioning
confidence: 90%
“…Greater than typical grain yields (∼ 4 Mg ha −1 ) in 2010 were observed in this experiment as well as throughout most of Northwest Minnesota (Table 3). Earlier research in Northwest Minnesota (Farmaha and Sims, 2013a, 2013b) showed that years having adequate precipitation, uniform precipitation distribution (Fig. 1), and favorable temperatures throughout the growing season (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The promotion effect was significant when drought was severe in the early growth stages in 2017; thus, a higher GY for CRU was observed than for U. Nevertheless, controlled release urea can be more expensive than conventional urea, hindering its widespread use (Farmaha and Sims, 2013), although one application of controlled release urea is the better choice to ensure that the crop is not short of N at the late stage of growth, with reduced fertilization damage to maize and increased time and labor savings. Maximizing agronomic and economic benefits should be constantly considered in agricultural production.…”
Section: Discussionmentioning
confidence: 99%